Research on Service Innovation of University Libraries in the Background of MOOC - Ding, Yi (IJRDO- Journal of Educational Research, 2017)
As a new mode of network teaching and education technology, MOOC makes extensive andprofound influence on education, and also brought great challenges to library service at the same time. This papermakes discussion on the impact of university library as well as measures on respond during in the MOOCenvironment.